Новые виды рода Philopterus (Mallophaga, Philopteridae) от каменок фауны СССР - Федоренко, И.А. (Вестник зоологии, 1983)
Four species of the genus Philopterus Nitzsch, 1818 are described
as new: Ph. oenanthe sp. n. from common wheatear, Ph. pleschankae sp. n. from pied
wheatear, Ph. belskayae sp. n. from Finsch's wheatear, ‘and Ph. picatae sp. n. from Eastern
pied wheatear. Diagnostic characters of described species and Ph. isabellinae (Mey, 1982) from Isabelline wheatear are given.